Medication-related osteonecrosis of the jaw, osteoradionecrosis, and osteomyelitis: A comparative histopathological study - De Antoni,Carlos Cesar (2018)
Abstract It is largely known that some oral diseases can be diagnosed based upon their clinical manifestation combined with the patient's medical history and generally not depending on examination. This is the case of some bone diseases such as osteoradionecrosis of the jaw (ORNJ), osteomyelitis of the jaw (OMJ), and medication-related osteonecrosis of the jaw (MRONJ). The present study aimed to analyze the histopathological features of these specific bone diseases in order to evaluate similarities and differences. Forty-four bone specimens resected from each bone disease (22 cases of ORNJ, 6 cases of OMJ, and 16 cases of MRONJ) were analyzed by two experienced oral pathologists without prior knowledge of the diagnosis, considering bone tissue condition, inflammation, vascularization, and the presence of microorganisms. In addition, the examiners formulated a diagnostic hypothesis for each specimen. Many histopathological similarities were found among the diseases, especially considering the presence of necrotic bone, inflammation, and microorganisms. Statistically significant differences were detected in empty bone lacunae, which was decreased in ORN (p = 0.042), and considering neutrophil count, which was low in the MRONJ group (p ≤ 0.001). The Kappa coefficient was calculated and agreement was detected based on the histopathological parameters, but not for diagnostic suggestion (p=0.23). In conclusion, histopathological aspects of ORNJ, OMJ, and MRONJ do not permit a conclusive diagnosis, emphasizing the necessity of a detailed clinical report.